16 THE PREVALENCE OF NEUROPSYCHIATRIC SYMPTOMS IN MILD COGNITIVE IMPAIRMENT: A POPULATION-BASED STUDY. (1st March 2006) - Geda, Y. E.; Rocca, W. A.; Knopman, D. S.; Roberts, R.; Petersen, R. C.
Abstract : Objective: To estimate the prevalence of neuropsychiatric symptoms among subjects with mild cognitive impairment (MCI) in a defined population. Background: The population-based prevalence of neuropsychiatric symptoms in MCI is unknown except for a recent report (Lyketsos et al, 2002, JAMA) that has not yet been replicated. Design/Methods: The Mayo Clinic Study of Aging is an NIH-funded population-based study that was launched in October 2004. It is designed to estimate the prevalence and incidence of MCI. Elderly individuals of age 70 to 89 years are being recruited by using a stratified random sampling from the target population of Olmsted County, Minnesota (equal allocation of men and women). All participants undergo neurological, neuropsychiatric, and psychometric evaluations. A consensus panel of behavioral neurologists, geriatrician, neuropsychiatrist, neuropsychologists, and nurses determined the classification of normal cognitive aging, MCI, or dementia based on standard definitions. The Neuropsychiatric Inventory (NPI) was administered to all participants, and the prevalence of symptoms in MCI cases was compared to cognitively normal individuals (controls), matched by age and gender (1 case to 3 controls), by using chi-square or Fisher's exact test. Results: Neuropsychiatric data were available on 104 participants with MCI and 312 cognitively normal individuals. The prevalence of apathy was 24% in MCI ( n = 25/104) vs 6.1% (19/312) in cognitively normal individuals ( p < .0001). Similarly, there were significant differences in the prevalence of depression 26% vs 11.5% (p = .0004), anxiety 11.5% vs 3.9% (p = .004), and irritability 18.3% vs 8.7% (p = .007). Conclusions: The prevalence of neuropsychiatric symptoms in our study is comparable to the published report (Lyketsos et al, 2002) that used a similar design (population based) and measurement instrument (NPI); however, we report a slightly higher frequency of apathy and depression. One major finding of our study is that apathy may be the most distinguishing neuropsychiatric feature between MCI and normal cognitive aging, and this, in turn, may have an implication for a future interventional study that can target apathy in order to delay the progression of MCI to dementia.